Evaluation of behavior in veal calves fed milk containing different levels of hempseed cake (Cannabis sativa L.) - Arango, Sheyla; Guzzo, Nadia; Trabacchin, V.; Raffrenato, Emiliano; Sartori, Cristina; Bailoni, Lucia (Frontiers in Veterinary Science, 2023)
The aim of the study was to evaluate the effect on behavior patterns of veal calves fed with increasing levels of hempseed cake (HSC) diluted in the milk replacer. Forty-eight (12 females and 36 males) Belgian Blue veal calves (62.0 kg of body weight (BW) and 42.6 d of age) were offered the same type and quantity of solid and liquid feed twice a day, but randomly assigned to 1 of 3 different HSC inclusion levels: 0% (CTR), 3% (T3) and 6% (T6). The study lasted for 6 months, until slaughter. During this time, behavior was recorded using video cameras provided with a surveillance system. Results indicated that HSC had little effect on calves' behavior and that calves in general spend most of their time resting and ruminating as they normally do with conventional diets. Hempseed cake inclusion (T3 and T6) increased (P < 0.05) the appetite for solid food and licking behavior during the late afternoon. T3 female calves increased (P < 0.05) their movement in the late afternoon. Male calves decreased (P < 0.05) their positive interaction, movement and crosssucking in the late afternoon as the inclusion of HSC increased. The inclusion of HSC into veal calves' diet did not affect negatively the animals behavior so it can be suggested as a novel ingredient.